Innovation and the economics of healthcare: The case of blood cancer - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2016)
While innovation is central for the quality of healthcare and improving health outcomes, it is also a source of increasing costs for governments. Confronted by fiscal pressures, governments have made efforts to restrict access to innovative treatments. While such policies are understandable, they are not necessarily supportive of the ambition to control the cost burden of a disease. This paper reviews economic analyses of the cost burden of cancer, and blood cancers in particular, and the effects that innovative treatments have on other sources of costs in the healthcare system or the economy as a whole. While there is a need for more research on the relations between costs in healthcare systems, and significant variations between countries, several studies have found that access to innovative treatments have reduced inpatient care costs because, among other things, better treatments reduce the need for long hospital stay. Furthermore, research also shows that a significant part of the total cost burden of cancer and blood cancer is the productivity loss to the economy when patients are out of work. Reducing the productivity loss is central for improving the economic rationality of healthcare systems. This Policy Brief charts some areas for work - at national and the EU level.
Keywords: 330; Gesundheitskosten; Krebskrankheit; Medizinische Behandlung; Innovation; Gesundheitsfinanzierung; EU-Staaten